A Thousand kilometres beyond the Yellow river - Kamamoto, Tatsuya; Kawasaki, Masamori; Noguchi, Tokutaro; Tamai, Isao (The Silk Road, 1990)
Explore the Yellow River on a goat-skin raft, the Buddha at Binglisi, the secret caves, He-Corridor, a battleground of the Huns which was bitterly conquered by the Chinese for the real treasure, the Heavenly Western Horses which gave the Huns their fearsome military power and the town of Zhang-ye, Nie pan Buddha, two hundred years old when Marco Polo lived here in the fourteenth century.